The Impact of Monetary and Fiscal Policies on Domestic Output: Evidence from ASEAN Economies - Dash, Tapas R. (International Journal of Economics and Financial Issues, 2025)
This paper investigates the impact of monetary and fiscal policies on domestic output in the ASEAN economies using a panel VAR approach. Among the five macroeconomic variables: gross domestic product (GDP), consumer price index (CPI), exchange rate (EXC), money supply (MS), and government expenditure (GEXP), two variables, such as MS and GEXP, are defined as policy variables. The CPI and EXC played as target variables for displaying external macroeconomic impacts. The model is estimated by the Generalized Method of Moments (GMM), where Helmert (forward mean-differencing) transformation is deployed to resolve individual heterogeneity and endogeneity problems. MS and GEXP (one lag) were positive and statistically significant, influencing GDP. On the other hand, higher CPI and EXC showed a negative effect on output, but a positive impact on GDP. Over 10 periods in advance, the explainable variance of GDP was 12.44% explained by government spending and 5.88% by money supply. By comparison, CPI and exchange rate effects supplied 39.05% and 12.40%, respectively. The results suggest that domestic policy actions as well as external macroeconomic conditions significantly influence economic performance among ASEAN countries.